2018
DOI: 10.21608/mjcu.2018.61490
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adropin Levels in a Preeclampsia Like L-Name Rat Model Treated with Sildenafil Citrate

Abstract: Background: Preeclampsia, a hypertensive disorder of pregnancy, is detrimental to both mother and fetus. Sildenafil been proposed as a potential therapy to reduce blood pressure and improve uteroplacental perfusion in preeclamptic patients. Adropin is a novel secreted energy homeostasis protein regulating carbohydrate, lipid and protein metabolism, maternal adropin levels in Preeclampsia were still controversy. Aim of the Work: To evaluate serum levels of adropin in preeclampsia-like rat model and in preeclamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(11 reference statements)
2
1
0
Order By: Relevance
“…These results are in line with animal studies by Raafat and Fathy [40] and human studies by Masuyama et al [49], which demonstrated that insulin resistance is associated with preeclampsia. Additionally, Thadhani et al [50] stated that women with low levels of PlGF, a surrogate insulin resistance marker, in the first trimester have an increased risk of developing subsequent PE.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with animal studies by Raafat and Fathy [40] and human studies by Masuyama et al [49], which demonstrated that insulin resistance is associated with preeclampsia. Additionally, Thadhani et al [50] stated that women with low levels of PlGF, a surrogate insulin resistance marker, in the first trimester have an increased risk of developing subsequent PE.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with animal studies by Raafat and Fathy [40] and human studies by Carty et al [41] and Khoury et al [42], which demonstrated that the lipid levels in women with preeclampsia are higher than those in healthy pregnant women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation